Establishment of Wind Gust Estimation Equation in Bohai Sea - Hu, Haichuan; Huang, Bin; Dai, Kan; Qu, Hongyu (Frontiers in Earth Science, 2022)
Wind gusts over the ocean can have a great influence on maritime transport and production operations. However, due to the scarcity of marine observation data and the complex causes of wind gusts, the estimation and forecasting of gusts at sea are even more difficult. In this paper, a gust estimation equation applicable to the Bohai Sea is established based on the observation and reanalysis data, with representative observation stations on the coast and offshore in the Bohai Sea. During the process, partial correlation analysis and a significance of correlation coefficient difference test were used to further clarify the influence of average wind speed and vertical wind shear at different heights on wind gusts. The final gust estimation equation includes a mean wind speed term, a turbulence term and a convection term, which are statistically significant contributors; also there are clear physical meanings. Comparing two gust factor methods in this paper, the average errors and fitting errors of the least squares gust estimation equation are the smallest. For wind gusts between 10m/s and 26m/s the fitting error in the gust estimation equation is 7.68%-12.25% and 21.10%-30.08% lower than that of two gust factor methods in this paper. The gust estimation equation better reflects the difference of wind gusts typical under different average wind speeds and vertical wind shear conditions, so a better prediction for wind gusts can be achieved.